Associations between Thyroid Hormones, Calcification Inhibitor Levels and Vascular Calcification in End-Stage Renal Disease. - Christiaan Lucas Meuwese; Hannes Olauson; Abdul Rashid Qureshi; Jonaz Ripsweden; Peter Barany; Cees Vermeer; Nadja Drummen; Peter Stenvinkel (PLoS ONE, 2015)
Vascular calcification is a common, serious and elusive complication of end-stage renal disease (ESRD). As a pro-calcifying risk factor, non-thyroidal illness may promote vascular calcification through a systemic lowering of vascular calcification inhibitors such as matrix-gla protein (MGP) and Klotho.In 97 ESRD patients eligible for living donor kidney transplantation, blood levels of thyroid hormones (fT3, fT4 and TSH), total uncarboxylated MGP (t-ucMGP), desphospho-uncarboxylated MGP (dp-ucMGP), descarboxyprothrombin (PIVKA-II), and soluble Klotho (sKlotho) were measured. The degree of coronary calcification and arterial stiffness were assessed by means of cardiac CT-scans and applanation tonometry, respectively.fT3 levels were inversely associated with coronary artery calcification (CAC) scores and measures of arterial stiffness, and positively with dp-ucMGP and sKlotho concentrations. Subfractions of MGP, PIVKA-II and sKlotho did not associate with CAC scores and arterial stiffness. fT4 and TSH levels were both inversely associated with CAC scores, but not with arterial stiffness.The positive associations between fT3 and dp-ucMGP and sKlotho suggest that synthesis of MGP and Klotho is influenced by thyroid hormones, and supports a link between non-thyroidal illness and alterations in calcification inhibitor levels. However, the absence of an association between serum calcification inhibitor levels and coronary calcification/arterial stiffness and the fact that MGP and Klotho undergo post-translational modifications underscore the complexity of this association. Further studies, measuring total levels of MGP and membrane bound Klotho, should examine this proposed pathway in further detail.